Malnutrition and its associated factors among people living with HIV/AIDS (PLHIV) in resource limited settings: A single-centred study - Muktar Musa Shallangwa; Nathan Isaac Dibal; Mukund Bhandari; Shuaibu Saidu Musa; Hassan Muhammad Bello (Clinical Epidemiology and Global Health, 2023)
Objectives: The objective of this study was to determine the prevalence and factors associated with malnutrition among PLHIV accessing ART at Muhammad Shuwa Memorial Hospital (MSMH). Methods: A facility-based cross-sectional study recruited 384 PLHIV accessing ART at MSMH using convenience sampling. Heights and weights were measured in metre (m) and kilogram (kg) respectively to determine body mass index (BMI). BMI <18.5 kg/m2 indicated undernourishment, and BMI >25.5 kg/m2 indicated overweight/obesity. Results: The prevalence of undernutrition and overnutrition among participants was 13% and 30.2%, respectively. Factors such as being female (AOR = 17.72; 95% CI: 4.214–74.548), aged 30 years and above (AOR = 9.87; 95% CI: 2.984–32.631), being unmarried (AOR = 0.34; 95% CI: 0.122–0.936), having a monthly income of N30,000 or higher (AOR = 0.34; 95% CI: 0.122–0.936), having a WHO clinical stage 2 and above (AOR = 35.9; 95% CI: 6.061–212.596), having a viral load of 1000cp/ml or higher (AOR = 4.95; 95% CI: 1.136–21.576), being on ART for 5 years and above (AOR = 0.01; 95% CI: 0.002–0.06), and having inadequate dietary diversity (AOR = 0.03; 95% CI: 0.003–0.18) were associated with undernutrition. On the other hand, factors such as being aged 30 years and above (AOR = 6.68; 95% CI: 2.261–22.845), being unemployed (AOR = 2.833; 95% CI: 1.419–5.984), being on DTG-based regimen (AOR = 0.025; 95% CI: 0.003–0.101), not experiencing eating difficulties (AOR = 11.53; 95% CI: 1.706–254.494), and having inadequate dietary diversity (AOR = 0.200; 95% CI: 0.105–0.371) were associated with overnutrition. Conclusion: Prevalence of both undernutrition and overweight or obesity is observed among PLHIV at MSMH. Consequently, it is essential to include nutrition education as an integral component of the comprehensive care provided to PLHIV.